Efficient Preparation of Cyclic α-Alkylidene β-Oxo Imides by Using a Flow Microreactor System - Komuro, Katsuhiro; Nagaki, Aiichiro; Shimoda, Hiroki; Uwamori, Masahiro; Yoshida, Jun-ichi; Nakada, Masahisa (Synlett, 2018)
Successful transformations of 3-iodo-1-methyl-5,6-dihydropyridin-2(1H)-one into its derivatives by a halogen–lithium exchange and subsequent reactions in a flow microreactor system are described. The methylation of the organolithium compound generated from 3-iodo-1-methyl-5,6-dihydropyridin-2(1H)-one in the flow microreactor system afforded the desired methylated product in 68% yield, whereas the yield of the corresponding batch reaction was 23%. This superiority of the flow microreactor system was further emphasized in the reaction of the organolithium compound with methoxycarbonyl isocyanate, which gave the desired imide in 78% yield by using the flow microreactor system whereas the yield of the corresponding batch reaction was only 2%. The established flow microreactor system was also effectively used for the reaction of the organolithium compound with phenyl isocyanate to afford the desired product in 52% yield.
Keywords: flow microreactor system; halogen–lithium exchange reaction; lithiation; imides; isocyanates; methylation